Analisis Kebutuhan Pengembangan Media Virtual Reality Sistem Pencernaan untuk Meningkatkan Berpikir Kritis Kelas V SD - Dhea Annisa Oktarizka; Yunus Abidin (Elementary Teacher Education Program, Majalengka University, 2024)
Learning media is an important part as a means so that students can understand the material well. However, in reality, sometimes the media used is not appropriate, which has an impact on students' lack of attention, low learning outcomes and lack of attainment of 21st century skills. The ability to think critically is one of the 21st century skills. The digestive system is one of the materials in grade V school science. Base. The digestive process and diseases of the digestive system are still difficult for students to understand, this is because the material is presented only in book and power point teaching media. This is based on the results of observations and interviews with class V teachers. Meanwhile, the abstract digestive system material requires students' critical thinking skills. In stimulating critical thinking skills, students can utilize digital virtual Reality learning media. Virtual Reality media can visualize which students will experience directly. This research is quantitative descriptive research. With observations, interviews and surveys of 31 teachers at the Pal Merah District Elementary School, Jambi City. Thus, the aim of this research is to analyze the need for virtual Reality media to improve critical thinking skills regarding class V digestive system material.